Enduring Effects of Paternal Deprivation in California Mice (Peromyscus californicus): Behavioral Dysfunction and Sex-Dependent Alterations in Hippocampal New Cell Survival - Glasper, Erica R.; Hyer, Molly M.; Hunter, Terrence J. (Frontiers in Behavioral Neuroscience, 2018)
Early-life experiences with caregivers can significantly affect offspring development in human and non-human animals. While much of our knowledge of parent-offspring relationships stem from mother-offspring interactions, increasing evidence suggests interactions with the father are equally as important and can prevent social, behavioral, and neurological impairments that may appear early in life and have enduring consequences in adulthood. In the present study, we utilized the monogamous and biparental California mouse (Peromyscus californicus). California mouse fathers provide extensive offspring care and are essential for offspring survival. Non-sibling virgin male and female mice were randomly assigned to one of two experimental groups following the birth of their first litter: 1) biparental care: mate pairs remained with their offspring until weaning or 2) paternal deprivation (PD): paternal males were permanently removed from their home cage on postnatal day 1. We assessed neonatal mortality rates, body weight, survival of adult born cells in the dentate gyrus of the hippocampus, and anxiety-like and passive stress-coping behaviors in male and female young adult offspring. While all biparentally-reared mice survived to weaning, PD resulted in a ~35% reduction in survival of offspring. Despite this reduction in survival to weaning, biparentally-reared and PD mice did not differ in body weight at weaning or into young adulthood. A sex-dependent effect of PD was observed on new cell survival in the dentate gyrus of the hippocampus, such that PD reduced cell survival in female, but not male, mice. While PD did not alter classic measures of anxiety-like behavior during the elevated plus maze task, exploratory behavior was reduced in PD mice. This observation was irrespective of sex. Additionally, PD increased some passive stress-coping behaviors (i.e., percent time spent immobile) during the forced swim task – an effect that was also not sex-dependent. Together, these findings demonstrate that, in a species where paternal care is not only important for offspring survival, PD can also contribute to altered structural and functional neuroplasticity of the hippocampus. The mechanisms contributing to the observed sex-dependent alterations in new cell survival in the dentate gyrus should be further investigated.